Professional Women in South African Pentecostal Charismatic Churches. - Frahm-Arp, Maria (Studies of Religion in Africa Ser., 2010)
This book offers an exploration into the interconnections between career success and religiosity as it examines the role of Pentecostal Charismatic Christianity in the work experiences of young, professional, black women who are becoming part of the post-apartheid South African middle class.